Food item selection of Hanuman Langur (Presbytes entellus) in different season in Char-Koshe jungle of eastern Terai, Nepal - Adhikaree, Shaligram; Shrestha, Tej Kumar (Nepalese Journal of Biosciences, 2013)
Common langur was found to be a mixed feeder. 33 species of plants were found to be consumed and 16 more species were said to be consumed in that locality. Most of the plants were consumed during fruiting and flowering seasons. Most preferred (frequently used) plants were Terminalia belarica, Geruga pinnata, Spathalobus parviflora, Ficus bengalensis, Schlichera oleosa, Ficus glomerata, Diospyrus tomentosa, Terminalia tomentosa, Emblica officinalis etc. On the basis of time spent to consume, fruit and seed comprised of about 56%, flower, leaf-bud, young leaves 29%, and mature leaves, bark and petiole 15% of annual budget of diet. Amount of different items in different seasons vary according to availability of first item (fruits and flower) and second items (new growths and leaf-bud). Fruits constitute more than 83% of diet during month of monsoon. Insectivory was not observed except during grooming. The langurs were not reported to raid the crops in vicinity. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7476 Nepalese Journal of Biosciences 1: 96-103 (2011)